Analisis dan Perancangan Data Warehouse Sebagai Penunjang Penyusunan Instrumen Borang Akreditasi Program Studi - Darma, I Gede Wira; Wiharta, Dewa Made; Sastra, Nyoman Putra (Majalah Ilmiah Teknologi Elektro; Vol 21 No 1 (2022): (Januari - Juni) Majalah Ilmiah Teknologi Elektro, 2022)
Eligibility for Study Programs and Higher Education is determined based on the accreditation process. The accreditation criteria refer to the National Higher Education Standards. Nine standards that must be complete with documents in the accreditation process. The process of preparing form instruments is still done manually causing problems in the process of completing form instruments, because they have to recap a lot of data and require more time to retrieve and process the required data. To simplify the preparation of the form instrument, a data warehouse scheme and service-middleware built to collect the data needed in the preparation of the form instrument. The data warehouse schema design will use Kimball's Nine-Steps approach. Meanwhile, application development will use the Agile approach. The results of this research are in the form of data warehouse schema modeling in the Agile development process for the needs of study program accreditation forms.